Gallstone Ileus in Cipto Mangunkusumo General Hospital, Jakarta: A Case Series - Lalisang, Toar JM; Hehuwat, Georgina P.; Lalisang, Arnetta NL; Pratama, Irfan K.; Mazni, Yarman (The New Ropanasuri Journal of Surgery, 2019)
Introduction. Gallstone ileus is an uncommon mechanical bowel obstruction caused by a gallstone in the gastrointestinal tract which enters due to bile-enteric fistulae. This study aims to describe gallstone ileus and its management. Method. Data were retrospectively collected from medical records. Clinical manifestations, laboratory data, supporting radiographic examinations, treatment, postoperative care, and outcomes were collected. Results. We report two gallstone ileus cases at Cipto Mangunkusumo General Hospital, Jakarta which admitted in the last 20 years. The first case was a woman 33 years in 2002 and the second was man 45 years in 2017. Ileus was the main clinical symptoms. Gallstone ileus was diagnosed with preoperatively based on clinical and radiology findings. Laparotomy was performed and ileostomy for stones evacuation and cholecystectomy were performed without bile-enteric fistula repair. Large black stones were found at terminal ileum which made the obstruction. Conclusion. Gallstone ileus was an uncommon disease which can be treated and has a good prognosis. Plain abdominal x-ray has an important role in diagnosis and treatment approach.